1978
DOI: 10.1007/bf00329465
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase B (or II) in heat induced puffs of Drosophila polytene chromosomes

Abstract: Using indirect immunofluorescence visualization techniques we investigated the distribution of RNA polymerase B (or II) and histone H1 at heat shock puff loci in Drosophila melanogaster polytene chromosomes at different times during and after heat shock. After heat treatments of from 5 to 45 min, the heat shock puff displayed intense fluorescence when stained for RNA polymerase B, but relatively little fluorescence when stained for histone H1. Returning heat shocked larvae to room temperature resulted in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1979
1979
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…As a reaction to an environmental stress like heat shock, chromatin undergoes rapid and dynamic remodeling to turn off most of the gene expression and to turn on the genes specifically associated with heat shock responses (reviewed in reference 31). The induction of heat shock loci, which results in the synthesis of heat shock proteins and RNA, is accomplished by the recruitment of RNA pol II, transcription factors, and other chromosomal proteins including topo I to heat shock puffs (15,19,24,46,53,58). Our immunofluorescence data demonstrated that the topo I N-terminal sequence enables rapid mobilization of topo I to the heat shock puffs.…”
Section: Discussionmentioning
confidence: 69%
“…As a reaction to an environmental stress like heat shock, chromatin undergoes rapid and dynamic remodeling to turn off most of the gene expression and to turn on the genes specifically associated with heat shock responses (reviewed in reference 31). The induction of heat shock loci, which results in the synthesis of heat shock proteins and RNA, is accomplished by the recruitment of RNA pol II, transcription factors, and other chromosomal proteins including topo I to heat shock puffs (15,19,24,46,53,58). Our immunofluorescence data demonstrated that the topo I N-terminal sequence enables rapid mobilization of topo I to the heat shock puffs.…”
Section: Discussionmentioning
confidence: 69%
“…Heat shock in Drosophila results in a disappearance of most mRNAs and corresponding protein synthesis and the concomitant appearance of high levels of a few heat shock mRNAs and their corresponding heat shock protein products. This dramatic change in gene expression is accompanied by a rapid mobilization of Pol II and associated factors to a small number of heat shock loci, which can be visualized by immunofluorescent localization (17). If SRCAP is a general transcription coactivator for Pol II, we would expect to find it similarly concentrated at heat shock puff sites.…”
Section: Resultsmentioning
confidence: 99%
“…When DroiQo.hil flies, embryos, or tissue culture cells are removed from their normal environmental temperature and placed Instead at 370C, a distinct set of DNA sequences (those coding for the heat shock proteins [hsp]) rapidly become transcribed at a greatly Increased rate, while transcription of other genes Is reduced to very low levels (18,19). Immunofluorescence studies using antibodies to RNA polymerase 11 to stain polytene chromosomes have shown that most of the RNA polymerase molecules previously bound to transcribing regions are released by heat shock, and much of this polymerase subsequently binds to the heat shock loci (20,21). Because of the rapid, qualitative alterations in gene expression afforded by heat shock, this has been used to study many aspects of gene expression, particularly the nuclear conformation of genes as monitored by sensitivity to nucleases.…”
Section: Introductionmentioning
confidence: 99%